Bioprospecting of a Native Plant Growth-Promoting Bacterium Bacillus cereus B6 for Enhancing Uranium Accumulation by Sudan Grass (Sorghum sudanense (Piper) Stapf) - Longyuan Wu; Lijuan Zhang; Ning Wang; Wei Huang; Yanzhi Wang; Meng Sun; Guofeng Zheng; Wei Wang; Chong Shi (Biology)
Phytoremediation technology is viewed as a potential solution for addressing soil uranium contamination. Sudan grass (Sorghum sudanense (Piper) Stapf.), noted for its robust root structure and resilience to heavy metals, has garnered significant attention. This paper investigates a strain of uranium-tolerant bacterium, B6, obtained from the inter-root environment of native plants in soil contaminated with uranium tailings. The bacterium was identified as Bacillus cereus. Genomic analyses and assessment of uranium tolerance-promoting properties showed that strain B6 not only exhibited high uranium tolerance, but also possessed beneficial properties such as phosphorus solubilization and iron-producing carriers. In this study, we used strain B6 as an inoculant in combination with Sudan grass for germination and potting experiments. The findings demonstrated that Bacillus cereus B6 could substantially mitigate the adverse effects of uranium stress on Sudan grass, boost the plant’s antioxidant response, significantly increase the root length and dry biomass of Sudan grass, and facilitate the accumulation of uranium in the roots, as well as its translocation to the aboveground portions. The study showed that PGPB strain B6 can significantly enhance the effect of plant accumulation of uranium and increase the potential of Sudan grass to become a uranium-rich plant, which provides an important scientific basis and application prospect for the use of microbial-assisted Sudan grass remediation technology to treat uranium-contaminated soil.